Beyond Geometric Effects: Particle Size-Dependent Electronic Promotion in Ru Catalysts for Ammonia Synthesis - Yaejun Baik; Seunghyuck Chi; DongHwan Oh; Susung Lee; Kyeongjin Lee; Chanyoung Oh; Minho M. Kim; Dooam Paik; Minju Chung; Hyungjun Kim; Minkee Choi (Journal of the American Chemical Society, 2026)
Abstract Metal particle-size effects in heterogeneous catalysis are commonly interpreted in geometric terms, where catalytic trends arise from variations in the density of active surface ensembles while the intrinsic properties of the sites are generally assumed to remain unchanged. Here we demonstrate that metal particle size also governs the intrinsic properties of active sites via size-dependent electronic promotion, beyond conventional geometric effects. Using well-defined Ru catalysts supported on multiwalled carbon nanotubes for ammonia synthesis, we separate the geometric contribution of B5-like site density from changes in the intrinsic properties of the sites induced by electronic promotion. Without promoters, the adsorption and catalytic properties of these sites remain essentially invariant with particle size, consistent with classical geometric interpretations. In contrast, with electronic promotion using BaO, interfacial charge storage and capacitive effects enable smaller Ru particles, with higher surface-to-volume ratios, to accumulate greater electron densities. This size-dependent electronic enrichment directly tunes the intrinsic reactivity of individual B5-like sites, strengthening N2 activation through enhanced π-backdonation and alleviating hydrogen poisoning, leading to higher site-specific activity. These findings establish particle size as a dual control parameter that modulates both site density and intrinsic site properties via electronic effects, providing new insight into the complex interplay between catalyst structure, charge distribution, and intrinsic catalytic activity.